Are long-distance dispersal syndromes associated with the conservation status of plant species? The Canary Islands as a case study - Coello, Alberto J.; Leo, María; Arjona, Yurena; Vargas, Pablo (Mediterranean Botany, 2018)
Dispersal is the process that allows organisms to reach new suitable territories and expand their area of occupancy. In plants, long-distance dispersal (LDD) of diaspores is related to the presence of morphological structures (dispersal syndromes) that favor mobility by wind (anemochorous), sea currents (thalasochorous) and animals (epizoochorous and endozoochorous). The relationship between these LDD structures and the distribution of plant species is related to characteristics of different archipelagoes. Previous studies in several archipelagoes found that the Canary Islands showed the strongest positive relationship between dispersal syndromes and species distributions. It has been long hypothesized that species without specialized structures for dispersal have more difficulties in expanding their areas of occupancy and consequently these species are more threatened because of limited distribution. Nevertheless, the effect of the dispersal ability of plant species on the degree of threat has never been tested in oceanic archipelagoes. In this study, we selected the 262 lowland endemic plant species of the Canary Islands and evaluated the relationship between the presence/absence of the four LDD syndromes and their threat status. A considerable number of threatened (154 spp.) and non-threatened (108 spp.) species were observed, of which 93 had LDD syndromes and 169 did not. Our analyses failed to find statistically significant differences between the number of threatened species with and without LDD syndromes and their IUCN threatened status. In sum, this study shows a poor contribution of dispersal abilities in the degree of threat of endemic plant species in the Canary Islands.